Value chain analysis of grass seeds in the drylands of Baringo County, Kenya: A producers’ perspective - Lugusa, Klerkson Okomboli; Wasonga, Oliver Vivian; Elhadi, Yazan Ahmed; Crane, Todd A. (Springer, 2016)
Pastoral households are increasingly practising fodder production in response to forage scarcity associated with land degradation, climate variability and change. Understanding the grass seed value chain is a prerequisite for developing sustainable fodder production and guiding appropriate out-scaling in the drylands. This study investigated the producers’ perspectives on grass seed production, marketing and challenges faced along the grass seed value chain in Marigat Sub-County of Baringo County, Kenya. The results show that the dominant actors were the bulking and processing agents who provided inputs and were a source of grass seed market to the producers. The producers preferred contractual agreements that allowed them to sell their grass seed to markets of their choice. As independent grass seed traders allowed for seed price negotiation, they were popular amongst the producers and thus handled the most volume of seeds marketed. Drought occurrence, inability of existing outlets to purchase grass seed at times, together with low prices offered for producers’ grass seed were found to be among the challenges facing the producers. There is need to strengthen the fodder groups with a possibility of registering them as cooperatives for the purpose of collective bargaining for better grass seed prices.